1998
DOI: 10.1023/a:1022548612107
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: These results demonstrate the safety and usefulness of laser methodology in preimplantation genetic diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(6 citation statements)
references
References 32 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Currently, PGS is performed in samples biopsied from polar bodies [ 10 - 13 ], cleavage embryos [ 14 , 15 ] or blastocysts [ 16 , 17 ]. It has been found that blastocysts have less mosaicism than cleavage embryos, thus most laboratories prefer blastocyst biopsy, in which multiple cells from the trophectoderm (TE) are biopsied and used for screening [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, PGS is performed in samples biopsied from polar bodies [ 10 - 13 ], cleavage embryos [ 14 , 15 ] or blastocysts [ 16 , 17 ]. It has been found that blastocysts have less mosaicism than cleavage embryos, thus most laboratories prefer blastocyst biopsy, in which multiple cells from the trophectoderm (TE) are biopsied and used for screening [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zona drilling using a laser is currently proposed as a technically easier method compared to mechanical and chemical means. Although there are reports that laser drilling does not impair embryonic development to the blastocyst stage and implantation [ 13 , 14 , 33 , 34 ], it has been postulated to pose potential harm to embryos in previous studies [ 31 , 35 , 36 ]. Furthermore, a laser is not cost-effective for IVF laboratories where PGD procedures are not performed frequently.…”
Section: Discussionmentioning
confidence: 99%
“…In countries where the genetic analysis of embryos is prohibited, polar body biopsy [47] (Figure 2b) is the only method of tissue sampling to screen for maternal mutations. If there are no legal restrictions, embryo biopsy at the cleavage stage (blastomere biopsy [48]) or at later stages of preimplantation development (trophectoderm [TE] biopsy [6]) can be performed.…”
Section: Ultrashort Laser Microsurgery Of Preimplantation Embryos For Application In Artmentioning
confidence: 99%